An Experimental and Analytical Study on the Bending Performance of CFRP-Reinforced Glulam Beams - Minjuan He; Yuxuan Wang; Zheng Li; Lina Zhou; Yichang Tong; Xiaofeng Sun (Frontiers in Materials, 2022)
The fiber-reinforced polymer is one kind of composite material made of synthetic fiber and resin, which has attracted research interests for the reinforcement of timber elements. In this study, 18 glued-laminated (glulam) beams, unreinforced or reinforced with internally embedded carbon fiber–reinforced polymer (CFRP) sheets, were tested under four-point bending loads. For the reinforced glulam beams, the influences of the strengthening ratio, the modulus of elasticity of the CFRP, and the CFRP arrangement on their bending performance were experimentally investigated. Subsequently, a finite element model developed was verified with the experimental results; furthermore, a general theoretical model considering the typical tensile failure mode was employed to predict the bending–resisting capacities of the reinforced glulam beams. It is found that the reinforced glulam beams are featured with relatively ductile bending failure, compared to the brittle tensile failure of the unreinforced ones. Besides, the compressive properties of the uppermost grain of the glulam can be fully utilized in the CFRP-reinforced beams. For the beams with a 0.040% strengthening ratio, the bending–resisting capacity and the maximum deflection can be enhanced approximately by 6.51 and 12.02%, respectively. The difference between the experimental results and the numerical results and that between the experimental results and analytical results are within 20 and 10%, respectively.